Literatura jako wehikuł tajemnicy. O pisarstwie Jerzego Grotowskiego - Kosiński, Dariusz (Przestrzenie Teorii, 2023)
Jerzy Grotowski (1933–1999), considered to be one of the greatest theatre artists of the 20th century, frequently expressed his ambivalent relation to words, repeating that any true knowledge has to be obtained by practice. However, all his life he had been creating and publishing text. The volume collecting them all in print has 1131 pages. Researchers interpreting his art (e.g. Krzysztof Rutkowski, Zbigniew Osiński) and his close collaborators like Ludwik Flaszen many times underlined the importance of Grotowski’s writings, stressing a special function the literature played in the artist’s research. Following their recognitions, partly polemizing with them, one can formulate some basic assumptions concerning the character and functions of Grotowski’s writing and its relation to the main aspects of contemporary literature. This was the man of theatre appears to be also an aware creator of a literature paradoxically close related and working for a mystery beyond the words.